Airfoil Anemometer With Integrated Flexible Piezo-Capacitive Pressure Sensor - Ramanathan, Arun K.; Headings, Leon M.; Dapino, Marcelo J. (Frontiers in Materials, 2022)
Demand is expected to accelerate for autonomous air vehicles that transport people and goods, making wind sensors on these vehicles and in the air space where they operate critical to ensure safe control of many simultaneous take-offs and landings. Conventional anemometers such as pitot tubes on airplanes as well as as other rotating, heated-element, acoustic, and drag technologies have drawbacks for small and micro-aerial vehicles including high power consumption, high aerodynamic drag, complex signal processing, and high cost. This paper presents an airfoil-shaped anemometer that provides low drag while integrating sensors for measuring wind speed and direction on tethered kites, balloons, and drones. Wind speed is measured by an integrated dual-layer capacitive pressure sensor with a polyvinylidene fluoride (PVDF) diaphragm while wind direction is measured by a 3D digital magnetometer that senses the orientation of the airfoil relative to the earth's magnetic field. A model is presented for a dual-layer capacitive sensor, used to design a sensor, and then validated through quasistatic pressure chamber testing. The capacitive sensor as well as a commercial digital magnetometer are integrated into a NACA~2412 profile airfoil and tested in a laboratory-scale wind tunnel. The capacitive sensor provides a sensitivity of 1.84~fF~m$^2$s$^{-2}$ and the airfoil exhibits a unique stable angle-of-attack to within $±$2$^°$ as measured by the magnetometer.